2006
DOI: 10.1021/es062081q
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Organosulfates in Secondary Organic Aerosol

Abstract: Recent work has shown that particle-phase reactions contribute to the formation of secondary organic aerosol (SOA), with enhancements of SOA yields in the presence of acidic seed aerosol. In this study, the chemical composition of SOA from the photooxidations of alpha-pinene and isoprene, in the presence or absence of sulfate seed aerosol, is investigated through a series of controlled chamber experiments in two separate laboratories. By using electrospray ionization-mass spectrometry, sulfate esters in SOA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

50
887
7
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 633 publications
(946 citation statements)
references
References 44 publications
50
887
7
2
Order By: Relevance
“…O rganonitrates (ON, i.e., RONO 2 ) and organosulfates (OS, i.e., ROSO 3 H) are known to be present in secondary organic aerosol (SOA) (1)(2)(3)(4), and are a nearly unexplored but potentially important aspect of atmospheric chemistry. The mechanisms behind ON and OS production and aging are poorly understood and generally ignored in models due in part to a lack of measurement approaches.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…O rganonitrates (ON, i.e., RONO 2 ) and organosulfates (OS, i.e., ROSO 3 H) are known to be present in secondary organic aerosol (SOA) (1)(2)(3)(4), and are a nearly unexplored but potentially important aspect of atmospheric chemistry. The mechanisms behind ON and OS production and aging are poorly understood and generally ignored in models due in part to a lack of measurement approaches.…”
mentioning
confidence: 99%
“…OS (i.e., ROSO 3 H) have been observed in both laboratorygenerated and ambient organic aerosol (OA) using negative ion (−) electrospray ionization (ESI)-MS techniques, resulting in the understanding that OS form in ambient aerosol from the oxidation of biogenic VOC in the presence of acidified sulfate aerosol (4,20). Although their prevalence in ambient aerosol remains unclear, further evidence for substantial OS contributions to SOA come from rainwater studies (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of aerosol as seed particles seems to be necessary (Surratt et al, 2010;Lin et al, 2012), but also the 25 acidity of aerosol can influence the formation yield of IEPOX-SOA. Laboratory and field studies found a correlation between IEPOX-SOA and sulfate, which is related to the acidity of aerosol (Surratt et al, 2007;Budisulistiorini et al, 2013). Although the IEPOX pathway is considered as the dominant one, further laboratory studies show that also other gas-phase reactions of ISOPOOH with multifunctional hydroperoxides contribute to the formation of isoprene-derived SOA (e.g., Krechmer et al, 2015;Liu et al, 2016b;Riva et al, 2016).…”
mentioning
confidence: 99%
“…to particle acidity, which enhances isoprene SOA formation through acid-catalyzed reactive uptake and multiphase chemistry of IEPOX and MAE (Surratt et al, 2007Gaston et al, 2014;Riedel et al, 2015), while NO x determines whether the oxidation pathway leading to IEPOX or MAE/HMML predominates (Lin et al, 2013b;. Isoprene SOA comprises a large portion of global atmospheric fine particles (PM 2.5 , aerosol with aerodynamic diameters ≤ 2.5 µm) (Carlton et al, 2009;Henze et al, 2008), but few studies have focused on its health implications .…”
mentioning
confidence: 99%